Wicked river : a novel - Milchman, Jenny (Sourcebooks Landmark, 2018)
Six million acres of Adirondack forest separate Natalie and Doug Larson from civilization. For the newlyweds, an isolated backcountry honeymoon seems ideal. But just as Natalie and Doug begin to explore the dark interiors of their own hearts, as well as the depths of their love for each other, it becomes clear that they are not alone in the woods. A man watches them, wielding the forest like a weapon. He wants something from them more terrifying than death. And once they are near his domain, he will do everything in his power to make sure they never walk out again. -- adapted from jacket